Celiac Plexus Cryoneurolysis - Chary, Aron; Edalat, Faramarz (Seminars in Interventional Radiology, 2022)
Intractable, chronic abdominal pain from upper abdominal malignant and benign diseases is a significant challenge for healthcare providers and burden on the healthcare system. While opioid analgesics are commonly used to provide pain relief, the adverse effects of chronic opioid use cannot be overlooked. Celiac plexus neurolysis via chemical or thermal means represents an alternative minimally invasive approach to provide palliative pain relief and increase patients' quality of life. Through the use of computed tomography guidance, celiac plexus neurolysis can be performed by accurately targeting the celiac plexus, while minimizing risks to adjacent structures. Historically, celiac plexus neurolysis was performed via instillation of ethanol or phenol; however, within the past decade cryoablation has gained increasing use with potentially fewer side effects.
Keywords: celiac plexus; malignancy; cryoablation; neurolysis; pain management; interventional radiology